Performance and Scalability Analysis of Ethereum and Hyperledger Fabric - Yusuf Ucbas; Amna Eleyan; Mohammad Hammoudeh; Manar Alohaly (IEEE Access, 2023)
Blockchain emerged in the last decade as a promising technology with possible applications in numerous fields such as healthcare, supply chain, and finance. Its immutability, transparency, security, and decentralisation gained significant attention in academia and industry. One technology that blockchain can support is the Internet of Things (IoT). However, there are still challenges hindering the real-world adoption of blockchain due to concerns about its performance, scalability, and complexity. This study contributes to a comparative study that analyses blockchain platforms in terms of their performance and scalability, with specific reference to IoT applications. We focus on the Ethereum and Hyperledger Fabric blockchain platforms. As part of the implementation, an IoT healthcare use case is developed. We conducted performance and scalability tests on private platform networks to measure the throughput and latency parameters. To evaluate scalability, we examined the behaviour of the studied platforms in response to an increase in the number and rate of transactions. Hyperledger Caliper is used to collect these parameters. Experiment analysis shows that Fabric outperforms Ethereum in terms of latency and throughput. As for performance and scalability analysis, Fabric was found to be more suitable than Ethereum for private networks such as IoT healthcare ecosystems.